Constructionism for language immersion: A case study of Thai education development - Manissaward Jintapitak (2018)
© 2017 American Scientific Publishers All rights reserved. For Thailand, English as a second language is a necessary medium for knowledge transfer and life-long learning in the 21st century. Thailand fell to 62nd out of 70 nations in English proficiency and is now the third-worst country in Asia on Education First’s Annual English Proficiency Index. Theoretically for children, ages 6–8 years, are the best period for learning a second language regarding the student’s physical development. But, in fact, Thai students, in rural areas outside Bangkok cannot use their English skills to communicate effectively with English speaking people, due to the following reasons: the quality of the teacher and the learning materials and the lack of an individual interactive learning corner. This research aims to study the use of total language immersion in the classroom so that students can communicate primarily with particular emphasis on listening and speaking skills applying a preliminary discussion. The experiment and learning observation was carried out for four weeks. Smart classroom and infrastructure were implemented, teachers facilitated the skills of the students by the total immersion technique and by constructive teaching methods. There are four total immersion elements for students to increase their listening-speaking skills: the total immersion pedagogy by a native teacher, tablet-technology, contents-application and facilitators. However, for primary school students, a facilitator, who encourages and conducts the appropriate total immersion classroom environment, is the most important factor. Students were confident to start learning in total language immersion, and the performance of students improved during four weeks. The differences of the teacher’s characteristics and their mental model of immersion techniques with smart classroom equipment affect the success of the language communication skills of primary students. Conducted and encouraged by a facilitator, students increase their leaning abilities and confidence in the total immersion environment.